2020
DOI: 10.3390/soc10020043
|View full text |Cite
|
Sign up to set email alerts
|

Two Types of Support for Redistribution of Wealth: Consistent and Inconsistent Policy Preferences

Abstract: This article aims to clarify the latent structure of support for redistribution. To this end, the author analyzed data from the National Survey of Social Stratification and Social Mobility in 2015 (SSM 2015), which was conducted in Japan, using finite mixtures of regression models. The results revealed that the population could be categorized into two latent groups: one that determines preferences for social policies based on self-interest and another that does so based on ideology. Surprisingly, the results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Formally, the correlation between actual and perceived mobility at the state level is −0.3 ( p-value of 0.047). 15 The bottom right panel of Figure 6 shows the degree of over-optimism relative to the national average in the US, not relative to the mobility in the state. The same patterns are apparent, suggesting that states that are more over-optimistic relative to state-level mobility are also more over-optimistic relative to the national mobility level.…”
Section: Geography Of Perceptions In the United Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Formally, the correlation between actual and perceived mobility at the state level is −0.3 ( p-value of 0.047). 15 The bottom right panel of Figure 6 shows the degree of over-optimism relative to the national average in the US, not relative to the mobility in the state. The same patterns are apparent, suggesting that states that are more over-optimistic relative to state-level mobility are also more over-optimistic relative to the national mobility level.…”
Section: Geography Of Perceptions In the United Statesmentioning
confidence: 99%
“…Newman, Johnston, and Lown (2015) document the link between local inequality and the belief that the United States is a meritocracy 15. This relation is not driven by the Southeastern states.…”
mentioning
confidence: 93%
“…Even though the policy preferences of Japanese people are seemingly inconsistent, it does not imply that they are irrational. As elucidated in previous studies (Koos and Sachweh, 2017;Sudo, 2020), support for redistribution and free competition are not necessarily irreconcilable. Contrarily, it should be noted that the mean of support for redistribution is lower than the support for free competition.…”
Section: Analytic Strategymentioning
confidence: 72%
“…In this vein, research suggests that support for redistribution can be understood through different latent dimensions. For instance, survey data from Japan showed that support for redistribution can be grouped into two kinds of latent profiles: one group endorsed redistribution motivated by economic self-interest, and another group motivated by ideologies (Sudo, 2020 ). Similarly, Jordan ( 2018 ) differentiates between people's belief in the responsibility of the government to reduce inequality—the overall desire for the government to intervene—and preferences for social spending programs—the need to address specific social policy areas (e.g., unemployment, health care).…”
Section: Introductionmentioning
confidence: 99%